SEF: A Secure, Efficient, and Flexible Range Query Scheme in Two-Tiered Sensor Networks - Jiajun Bu; Mingjian Yin; Daojing He; Feng Xia; Chun Chen (International Journal of Distributed Sensor Networks)
Large-scale wireless sensor networks follow the two-tiered architecture, where master nodes take charge of storing data and processing queries. However, if a master node is compromised, the information stored in it may be exposed, and query results can be juggled. This paper presents a novel scheme called SEF for secure range queries. To preserve privacy, SEF employs the order-preserving symmetric encryption which not only supports efficient range queries, but also maintains a strong security standard. To preserve authenticity and integrity of query results, we propose a novel data structure called Authenticity & Integrity tree. Moreover, SEF is flexible since it allows users to include or exclude the authenticity and integrity guarantee. To the best of our knowledge, this paper is the first to use the characteristic of NAND flash to achieve high storage utilization and query processing efficiency. The efficiency of the proposed scheme is demonstrated by experiments on real sensor platforms.